2008
DOI: 10.1016/j.cellbi.2008.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin protects PC12 cells against β‐amyloid‐induced cell injury

Abstract: beta-Amyloid protein (Abeta), a major protein component of brain senile plaques in Alzheimer's disease, is known to be directly responsible for the production of reactive oxygen species (ROS) and induction of apoptosis. In this study, the protective effect of puerarin, an isoflavone purified from the radix of the Chinese herb Pueraria lobata, on Abeta-induced rat pheochromocytoma (PC12) cultures was investigated. Although exposure of PC12 cells to 50 microM Abeta25-35 caused significant viability loss and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 38 publications
6
38
0
Order By: Relevance
“…32 Additionally, Puerarin from P. thunbergiana has been found to exert a neuroprotective effect against beta-amyloid-induced cell death in PC-12 cells. 33 Taken together, these findings and the results of the present study indicate that other unidentified constituents of the herbs in the PD-1 prescription may have participated synergistically in the neuroprotective action observed in the present study. Accordingly, future studies should be conducted to elucidate the neuroprotective mechanisms of PD-1.…”
Section: Discussionsupporting
confidence: 57%
“…32 Additionally, Puerarin from P. thunbergiana has been found to exert a neuroprotective effect against beta-amyloid-induced cell death in PC-12 cells. 33 Taken together, these findings and the results of the present study indicate that other unidentified constituents of the herbs in the PD-1 prescription may have participated synergistically in the neuroprotective action observed in the present study. Accordingly, future studies should be conducted to elucidate the neuroprotective mechanisms of PD-1.…”
Section: Discussionsupporting
confidence: 57%
“…An increasing body of evidence has indicated that puerarin has anti-apoptotic effects and mitigated apoptosis in multiple cell types, including neurons, microglia, osteoblasts and cardiomyocytes (8)(9)(10)(11). A previous study reported that puerarin protected PC12 cells against β-amyloid-induced cell injury, which was associated with its antioxidant effects (12). Another study confirmed that puerarin protected differentiated PC12 cells from H 2 O 2 -induced apoptosis via Akt phosphorylation (13).…”
Section: Introductionsupporting
confidence: 53%
“…Another study reported that puerarin exhibited a protective effect against the lipopolysaccharide (LPS)-induced apoptosis of H9c2 cardiomyocytes by reversing LPS-induced downregulation of Bax and upregulation of Bcl-2 (15). In addition, puerarin afforded protection against beta-amyloid-induced neurotoxicity by inhibiting apoptosis in PC12 cells, which contributed to activation of the PI3K-dependent signaling pathway in association with Akt phosphorylation (16). Although anti-apoptotic mechanisms have been demonstrated to be involved in the protective effect of puerarin in the nervous and cardiovascular system (17,18), in the present study, puerarin demonstrated antitumor effects by reducing cell viability and inducing cell apoptosis in SW1353 cells, which may be important for the clinical treatment of patients with cancer.…”
Section: Discussionmentioning
confidence: 99%